miR-103/107 regulates left-right asymmetry in zebrafish by modulating Kupffer’s vesicle development and ciliogenesis - Heigwer, Jana; Kutzner, Juliane; Jürgensen, Lonny; Katus, Hugo; Westhoff, Jens (Biochemical and biophysical research communications, 2020)
In zebrafish, cilia movement within the Kupffer’s vesicle (KV) generates a fluid flow responsible for accumulating nodal signals exclusively in the left lateral plate mesoderm, thereby initiating left-right patterning (LRP). Defects in LRP cause devastating congenital disorders including congenital heart malformations due to organ mis-positioning. We identified the miR-103/107 family to be involved in regulating LRP. Depletion of miR-103/107 in zebrafish embryos resulted in malpositioned and malformed visceral organs and hearts due to disturbed LRP gene expression, indicating early defects in LRP. Additionally, loss of miR-103/107 affected KV morphogenesis and cilia formation without disturbing endoderm development. Human fibroblasts depleted of miR-103a/107 often failed to extend cilia or developed shorter cilia, indicating functional conservation between species. We identified arl6, araf and foxH1 as direct targets of miR-103/107 providing a mechanistic link to cilia development and nodal signal titration. We describe a new microRNA family controlling KV development and hence influencing establishment of internal organ asymmetry.